Probiotics and Prebiotics as a Therapeutic Strategy to Improve Memory in a Model of Middle-Aged Rats - Romo-Araiza, Alejandra; Gutiérrez-Salmeán, Gabriela; Galván, Emilio J.; Hernández-Frausto, Melissa; Herrera-López, Gabriel; Romo-Parra, Hector; García-Contreras, Valentina; Fernández-Presas, Ana María; Jasso-Chávez, Ricardo; Borlongan, Cesar V.; Ibarra, Antonio (Frontiers in Aging Neuroscience, 2018)
Aging is associated with morphological, physiological and metabolic changes, leading to multiorgan degenerative pathologies, such as cognitive function decline. It has been suggested that memory loss also involves a decrease in neurotrophic factors, including brain-derived neurotrophic factor (BDNF). In recent years, microbiota has been proposed as an essential player in brain development, as it is believed to activate BDNF secretion through butyrate production. Thus, microbiota modulation by supplementation with probiotics and prebiotics may impact cognitive decline. This study aimed to evaluate the effects of probiotics and prebiotics supplementation on the memory of middle-aged rats. Sprague-Dawley male rats were randomized in 4 groups (n=13 per group): control (water), probiotic (E. faecium), prebiotic (agave inulin), symbiotic (E. faecium + inulin), which were administered for 5 weeks by oral gavage. Spatial and associative memory were analyzed using the Morris Water Maze (MWM) and Pavlovian autoshaping tests, respectively. Hippocampus was obtained to analyze cytokines (IL-1β and TNF-α), BDNF and GABA by ELISA. Butyrate concentrations were also evaluated in feces. The symbiotic group showed a significantly better performance in MWM (p<0.01), but not in Pavlovian autoshaping test. It also showed significantly lower concentrations of pro-inflammatory cytokines (p<0.01) and the reduction in IL-1β correlated with a better performance of the symbiotic group in MWM (p<0.05). Symbiotic group also showed the highest BDNF and butyrate levels (p<0.0001). Finally, we compared the electrophysiological responses of control (n=8) and symbiotic (n=8) groups. Passive properties of CA1 pyramidal cells exhibited changes in response to the symbiotic treatment. Likewise, this group showed an increase in the N-methyl-D-aspartate receptor (NMDA)/AMPA ratio and exhibited robust long-term potentiation (LTP) (p<0.01). Integrated results suggest that symbiotics could improve age-related impaired memory.